INTERNATIONAL TRADE, INTELLECTUAL PROPERTY RIGHT AND ECONOMIC DEVELOPMENT IN NIGERIA: IS THERE ANY LINK? - Amassoma, Ditimi; Ogbuagu, Matthew Ikechukwu; Niniola, Faith Esther (Journal of Business And Entrepreneurship, 2020)
This study explored on the nexus between trade (TRD), intellectual property right (IPR) and level of economic development (LDEV) over the period 1991 - 2018 using an Autoregressive distributed lag ARDL approach. The results suggest a long-run relationship between international trade, intellectual property right and level of economic development. The results also revealed that while the export component of the IPR exerted no impact on LDEV, TRD on the other hand, showed a temporary positive effect on the level of economic development possibly due to the instability in the macroeconomic environment and her overdependent on imported goods. Interestingly, FDI exerted a positive and significant effect on the level of economic development in the country. These results corroborate the outcome of the causality test, which revealed a uni-directional causality that runs from FDI, TRD to the level of economic development. In contrast, there seems to be a causal effect from the level of economic development to import component of the IPR to total productivity factor to inflation, respectively. The study concludes that both trade and intellectual property right are not capable of influencing economic development within the study period due to weak IPR protection and mono-product nature of the country. Based on the above, the study recommends that the government should provide an enabling environment that will further attract foreign investment in the country. Also, formulate a well developed institutional framework that will promote intellectual property right and finally diversify the economy into other sectors that are promising in order to avoid external shocks that can emanate from relying on a single sector of an economy.